2020
DOI: 10.5194/hess-24-3015-2020
|View full text |Cite
|
Sign up to set email alerts
|

Changing global cropping patterns to minimize national blue water scarcity

Abstract: Abstract. Feeding a growing population with global natural-resource constraints becomes an increasingly challenging task. Changing spatial cropping patterns could contribute to sustaining crop production and mitigating water scarcity. Previous studies on water saving through international food trade focussed either on comparing water productivities among food-trading countries or on analysing food trade in relation to national water endowments. Here, we consider, for the first time, how both differences in nat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…It has been predicted that about 59% of the global human population will face blue water scarcity by 2050 (Rockström et al 2009 ). It has been suggested that changing global cropping patterns may help minimize blue water scarcity (Chouchane et al 2020 ).…”
Section: Linking Blue and Green Water For Rice–fish Culturementioning
confidence: 99%
“…It has been predicted that about 59% of the global human population will face blue water scarcity by 2050 (Rockström et al 2009 ). It has been suggested that changing global cropping patterns may help minimize blue water scarcity (Chouchane et al 2020 ).…”
Section: Linking Blue and Green Water For Rice–fish Culturementioning
confidence: 99%
“…In this study, we defined "water supply constraints" as water consumption that must be reduced to mitigate regional water stress by one level in line with water stress index, which is categorized based on the ratio of water consumption to water availability for human, this index originate from and Mekonnen and Hoekstra (2016) , many previous publications has applied this index for their studies (e.g. Chouchane et al, 2020 ;. Ma et al, 2020 ;Zhuo et al,2016 ;Sun et al, 2016 ).…”
Section: Industrial Transition Scenarios For Evaluating Water Rationi...mentioning
confidence: 99%
“…Furthermore, regional impacts of crop production on ecosystems and freshwater resources can only be assessed by relating the total WF of production (agricultural, industrial, and domestic) to maximum sustainable levels within a given geographical unit (Bunsen et al, 2021;Hoekstra et al, 2012b;Liu et al, 2017;Hogeboom et al, 2020). WFs in crop growing areas that already overshoot (or soon to overshoot) these levels can be further assessed in ACEA to propose potential measures of WF reduction, such as more efficient irrigation and field management (Chukalla et al, 2015(Chukalla et al, , 2017Campbell et al, 2017;Nouri et al, 2019) or change of cropping patterns (Chouchane et al, 2020).…”
Section: Future Prospectsmentioning
confidence: 99%